Perceptions and experiences of healthcare workers during the COVID-19 pandemic in the UK. Issue 11 (5th November 2020) - Vindrola-Padros, Cecilia; Andrews, Lily; Dowrick, Anna; Djellouli, Nehla; Fillmore, Harrison; Bautista Gonzalez, Elysse; Javadi, Dena; Lewis-Jackson, Sasha; Manby, Louisa; Mitchinson, Lucy; Mulcahy Symmons, Sophie; Martin, Sam; et al.
Abstract : Objective: The COVID-19 pandemic has set unprecedented demand on the healthcare workforce around the world. The UK has been one of the most affected countries in Europe. The aim of this study was to explore the perceptions and experiences of healthcare workers (HCWs) in relation to COVID-19 and care delivery models implemented to deal with the pandemic in the UK. Methods: The study was designed as a rapid appraisal combining: (1) a review of UK healthcare policies (n=35 policies), (2) mass media and social media analysis of front-line staff experiences and perceptions (n=101 newspaper articles, n=1 46 000 posts) and (3) in-depth (telephone) interviews with front-line staff (n=30 interviews). The findings from all streams were analysed using framework analysis. Results: Limited personal protective equipment (PPE) and lack of routine testing created anxiety and distress and had a tangible impact on the workforce. When PPE was available, incorrect size and overheating complicated routine work. Lack of training for redeployed staff and the failure to consider the skills of redeployed staff for new areas were identified as problems. Positive aspects of daily work reported by HCWs included solidarity between colleagues, the establishment of well-being support structures and feeling valued by society. Conclusion: Our study highlighted the importance of taking into consideration the experiences and concerns of front-line staff during a pandemic. Staff working in the UK during the COVID-19 pandemic advocated clear and consistent guidelines, streamlined testing of HCWs, administration of PPE and acknowledgement of the effects of PPE on routine practice.